PENGARUH PERSEPSI NASABAH, KEPERCAYAAN NASABAH DAN LOYALITAS NASABAH TERHADAP PENGGUNAAN MOBILE BANKING (Studi Kasus Pada Bank Syariah Indonesia Kota Malang) - Namira Usman; Maslichah Maslichah; M Cholid Mawardi (El-Aswaq, 2020)
This study aims to determine the effect of customer perception, customer trust and customer loyalty on the use of mobile banking at Bank Syariah Indonesia Malang City The analytical method used in this study is multiple lmier regression analysis for hypothesis testing using SPSS. The results of this study indicate that the Perception variable Customer 1) has a partial negative and insignificant effect on the use of mobile banking (Y). Customer Trust Variable 2) and Customer Loyalty variable ) have a positive and partially significant effect on the use of mobile bankang (Y). Meanwhile, the variables of customer perception, customer trust and customer loyalty have a positive and significant effect simultaneously on the use of mobile banking.